1992
DOI: 10.1111/j.1365-2230.1992.tb02521.x
|View full text |Cite
|
Sign up to set email alerts
|

Practical use of a disability index in the routine management of acne

Abstract: We describe a brief questionnaire designed to assess the disability caused by acne. The questionnaire adds a patient-orientated dimension to medical records, high-lights patients with unusually high levels of disability, and increases the relevant information on which we base therapeutic decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
172
2
10

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(188 citation statements)
references
References 3 publications
4
172
2
10
Order By: Relevance
“…So, the fact that duration of the disease influences the level of anxiety and depression is consistent with the past study. 22 Motiley RJ et al 27 have reported reverse figures as compared to this study. Thus, the finding can vary in different studies.…”
Section: Discussioncontrasting
confidence: 51%
“…So, the fact that duration of the disease influences the level of anxiety and depression is consistent with the past study. 22 Motiley RJ et al 27 have reported reverse figures as compared to this study. Thus, the finding can vary in different studies.…”
Section: Discussioncontrasting
confidence: 51%
“…A higher score shows a very large impact on quality of life. 19 In our study a CADI score <8 is considered to have a small effect on quality of life & a score>8 is considered as having a larger effect on QOL. Both the questionnaires have Persian equivalents with confirmed reliability and validity.…”
Section: Methodsmentioning
confidence: 99%
“…A single physician recorded all the clinical observations using assessment scale ((Leeds count [16] and Cardiff Acne disability Index [17]). In this patient overall change in facial acne compared with his or her appearance at the beginning of study was made on the four point scale ranging from excellent to poor response.…”
Section: Clinical Evaluationmentioning
confidence: 99%